CATECHIZING THE HEAD AND THE HEART: AN INTEGRATED MODEL FOR CONFIRMATION MINISTRY - Salai, Sean M. (Heythrop journal, 2011)
In catechesis for adolescents seeking confirmation in the Roman Catholic Church, a dualistic bias unconsciously dichotomizes objective doctrine and subjective psychology. This is problematic because if a catechist does not communicate mind-independent truth, no seed of Catholic faith will have been planted in a student. At the same time, if a catechist does not affirm a student's subjectivity, the seed cannot find receptive soil. I believe the key to integrating these intellectual and affective elements – the head and the heart – lies in the link between what Bernard Lonergan calls authentic subjectivity and objectivity. Catechists can appeal to this link by embracing the moral responsibility to ‘know our knowing,’ becoming aware of our dualistic bias and judging our faith experiences according to objective standards of knowledge.